Avaliação do efeito da terapia com probiótico nos tecidos periodontais de ratos com periodontite induzida por ligadura - Rodrigues, Pedro Henrique De Carli (2019)
Probiotics are defined as living microorganisms which, when administered in suitable amounts, confer a benefit to the health of the individual. Bacteria of the genus Lactobacillus, Enterococcus and Bacillus are examples of probiotics. These appear to be a biological alternative to alter, at least in the short term, the plaque structure and help control periodontal disease (PD). Therefore, probiotics are now considered as a new therapeutic modality in the treatment of PD and studies are necessary to evaluate its effect. The objective of this study was to evaluate the effect of probiotic therapy on the periodontal and intestinal mucosa of rats with ligature-induced periodontitis. Thirty-two Wistar rats were randomly divided into 4 groups with 8 animals each: 1) Control group ): without periodontal disease and without administration of probiotic; 2) Periodontal disease group (PD): with periodontal disease induced and without administration of probiotic; 3) Probiotic group (PROB): without periodontal disease and with administration of probiotic; 4) Group periodontal disease + probiotic (DPPRO): with periodontal disease and administration of probiotic. The animals of the DP and DPPRO groups received a ligature in the lower first molars that acted as a gingival irritant for 44 days, favoring the accumulation of plaque and development of PD. Lactobacillus acidophilus probiotic was given orally for 44 days (8.0 x 107 CFU / mL), starting the same day as DP induction. After the experimental period, the animals were euthanized by guillotine decapitation. Blood was collected to assess triglyceride and total cholesterol concentrations. Hemi-mandibles were collected for histomorphometric and radiographic analysis. The duodenum was also removed for morphological evaluation and the gingival tissue around the molars was collected for analysis of the presence of interleukin 17 (IL-17). The data obtained were normal and were analyzed through ANOVA and Tukey post-test. The results of the total cholesterol and triglycerides dosage did not present statistically significant differences between the groups, as well as histomorphometric analyzes of the duodenum. Regarding the radiographic and histomorphometric analyzes of the mandible, the DPPRO group had a significantly lower bone loss than the DP group, as well as a lower number of osteoclasts in the DPPRO group when compared to the DP. There was a decrease in IL-17 in the DPPRO group when compared to the DP group. Based on the results obtained, it is suggested that Lactobacillus acidophilus-based probiotic therapy was effective in inhibiting the development of periodontitis by decreasing alveolar bone loss and modulating inflammation. However, it had no effect on the intestinal morphology of the duodenum